2021
DOI: 10.3390/ijerph18179055
|View full text |Cite
|
Sign up to set email alerts
|

Lead Pollution, Demographics, and Environmental Health Risks: The Case of Philadelphia, USA

Abstract: Lead (Pb) soil contamination in urban environments represents a considerable health risk for exposed populations, which often include environmental justice communities. In Philadelphia, Pennsylvania (PA), Pb pollution is a major concern primarily due to extensive historical Pb-smelting/processing activity and legacy use of Pb-based paints and leaded gasoline. The U.S. Environmental Protection Agency (USEPA) organized and/or compiled community-driven soil sampling campaigns to investigate Pb content in surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 79 publications
1
19
0
Order By: Relevance
“…The zip codes with the highest risk, that is, a high number of simultaneous lead‐risk factors, as identified by O’Shea et al. (2021) were zip codes 19121, 19125, 19132, 19133, 19134, 19138, 19140, 19141, 19143, and 19144 (Figure S2 in the Supporting Information ; see also O’Shea et al., 2021). Zip codes 19134 and 19125, however, were omitted from being a part of the area investigated here due to significant remediation work and research carried out in this region.…”
Section: Methodsmentioning
confidence: 93%
See 2 more Smart Citations
“…The zip codes with the highest risk, that is, a high number of simultaneous lead‐risk factors, as identified by O’Shea et al. (2021) were zip codes 19121, 19125, 19132, 19133, 19134, 19138, 19140, 19141, 19143, and 19144 (Figure S2 in the Supporting Information ; see also O’Shea et al., 2021). Zip codes 19134 and 19125, however, were omitted from being a part of the area investigated here due to significant remediation work and research carried out in this region.…”
Section: Methodsmentioning
confidence: 93%
“…The study area, broadly defined as West, North, and Upper North Philadelphia, was based on the results of a previous investigation, which analyzed lead risk at the zip code level within Philadelphia (O’Shea et al., 2021). Lead risk at the zip code level was determined by mapping various lead‐risk factors, including owner‐occupied units, renter‐occupied units, units built before 1980, demolitions, minority population (defined as racial and ethnic minorities within the United States), Black population, children in poverty, median income, EBLLs in children, number of smelters, and lead‐in‐soil data (O’Shea et al., 2021). A housing unit, as defined by the Census Bureau, is a house, an apartment, a group of rooms, or a single room intended to serve as a living quarter.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another similar study described the highest risk from metals (Pb, Cu, Zn, and Ni) in road sediment in tourism areas as opposed to residential, education, or high traffic-density areas (e.g., Wei et al, 2015), whereas a different assessment reported the highest metal (Pb, Cu, Zn, Co, V, Al, Ni, Cr, Cd) concentrations in industrial areas (e.g., Li et al, 2013). Indeed, a better knowledge of the spatial distribution of road sediment pollution and urban pollution in general is crucial to better understanding the risk it presents to human populations (e.g., O'Shea et al, 2020;O'Shea et al, 2021c).…”
Section: Spatial Variability Of Potentially Health-relevant Pollutantsmentioning
confidence: 99%
“…Although, in recent decades, overall lead exposure levels have been degraded, there is still a significant lead exposure problem among poor and underserved urban populations. When considering the influence of social factors on lead exposure, it is found that economic conditions, living conditions or ethnicities also affect the concentration of blood lead (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%